Acceptability of the Brushing RemInder 4 Good oral HealTh (BRIGHT) trial intervention: a qualitative study of perspectives of young people and school staff - Sarab Elyousfi; Nicola Innes; Heather Leggett; Hannah Ainsworth; Ivor G. Chestnutt; Peter Day; Mark Robertson; Sue Pavitt; Ian Kellar; Donna Dey; Zoe Marshman (BMC, 2022)
Abstract Background The Brushing RemInder 4 Good oral HealTh (BRIGHT) trial is investigating the clinical and cost-effectiveness of a multi-component behaviour change intervention to reduce the prevalence of dental caries in young people from deprived areas aged 11-13 years. Mobile health has gained popularity in delivering behaviour change interventions for improving oral health. The intervention, based on behaviour change theory, consists of two components; a single classroom-based session embedded in the school curriculum and a series of follow-up text messages (SMS) delivered twice daily to participants. This element of the process evaluation aimed to explore the acceptability of the BRIGHT intervention for pupils and school staff. Methods Qualitative study, based on the concept of acceptability. Focus groups were conducted with 50 pupils, from six secondary schools across the UK, who had received the intervention. Semi-structured interviews were conducted with 12 members of staff. Purposive maximum variation sampling was used. Interviews were transcribed verbatim and analysed using a framework approach. Results In line with the theoretical framework of acceptability, affective attitude, perceived effectiveness, ethicality, burden and self-efficacy were identified as factors that affect the acceptability of the BRIGHT intervention. Pupil participants appreciated learning about the consequences of inadequate brushing particularly the photographs of carious teeth during the classroom-based session. More detailed information on brushing techniques and follow-up lessons on oral health were recommended by pupils. In terms of the SMS, the data suggest that pupil participants found them to be helpful reminders for brushing their teeth. To further improve acceptability, more choice over the timing of the messages and greater interactivity to reduce tedium were suggested. Staff participants recognised the value of the lesson and reported that in general the content was suitable for their pupils. Having the lesson material prepared for them, having the necessary support and whether it was included in the curriculum, were factors that improved acceptability. Conclusion Overall, pupils and staff found the BRIGHT intervention acceptable and made some suggestions which could be adopted in any subsequent implementation of the intervention.